How a study on lived experiences impacted German occupation children – A mixed-method long-term approach - Kaiser, Marie; Glaesmer, Heide (Frontiers in Political Science, 2022)
Objective Research on the impact study participation has on participants has shown that, even though they may find it stressful during participation, overall, they appear to benefit personally and emerge with a positive cost-benefit-balance. In 2013, the first psychological study on German occupation children (GOC), a potentially vulnerable and hidden study population, was conducted, after which respondents shared a high volume of positive feedback. In the context of a follow-up survey, the impact of study participation on participants was investigated to determine the causes of this distinctly positive outcome. Methods Mixed-methods approach using the standardized Reactions to Research Participation Questionnaire (RRPQ) as well as open-ended questions on expectations toward participation, and changes due to participation in dealing with GOC background and in personal life. Analyses included N = 65 participants (mean age 68.92, 40% men) and were carried out with descriptive measures for RRPQ and inductive content analysis for open-ended questions. Results Participants specified six motives for participation besides answering the standardized form; 46.2% (n = 30) saw their expectations met. Although participation was related to negative emotions during participation, participants' overall experience was positive; 89.2% (n = 58) stated an inclination to participate again. 52.3% (n = 34) reported participation had helped develop new ways of dealing with their GOC experiences; five contributing factors were observed. Changes in private life were reported by 24.6% (n = 16); three aspects were identified. The vast majority (81.5%; n = 53) stated, following participation, they were able to disclose their GOC background to others. Participants placed emphasis on four aspects of this experience. Conclusion Although study participation was described as emotionally challenging during participation, participants felt that the overall impact it had on them was positive. The study was the first of its kind and thus presented an opportunity for a previously hidden population to step out of the dark, simultaneously gaining insight that helped them better understand themselves as GOC, and thereby increase their capacity for self-acceptance. Participants also benefitted from learning about the study's findings and connecting with other GOC through activities that ensued. In conclusion, results suggest that vulnerable and/or hidden populations benefit from specific attention to their lived experiences even at higher age.